2020
DOI: 10.1101/2020.04.03.20050195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Specimen Pooling to Conserve SARS CoV-2 Testing Resources

Abstract: Objectives To establish the optimal parameters for group testing of pooled specimens for the detection of SARS-CoV-2. Methods The most efficient pool size was determined to be 5 specimens using a web-based application. From this analysis, 25 experimental pools were created using 50 microliter from one SARS-CoV-2 positive nasopharyngeal specimen mixed with 4 negative patient specimens (50 microliter each) for a total volume of 250 microliter l. Viral RNA was subsequently extracted from each pool and tested us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(112 citation statements)
references
References 6 publications
5
107
0
Order By: Relevance
“…However, in a recent study, it has been documented that viral loads are similar in symptomatic and asymptomatic patients; thus, pool testing will produce similar results in all patients with COVID‐19 5 . The present study is concordant with the findings of Abdalhamid et al 6 who reported that pool testing is effective in saving resources in the population having prevalence less than 10%. Laboratories have begun to demonstrate that SARS‐CoV‐2 can be detected in RT‐qPCR performed on pooled samples, despite potential dilution.…”
Section: Discussionsupporting
confidence: 91%
“…However, in a recent study, it has been documented that viral loads are similar in symptomatic and asymptomatic patients; thus, pool testing will produce similar results in all patients with COVID‐19 5 . The present study is concordant with the findings of Abdalhamid et al 6 who reported that pool testing is effective in saving resources in the population having prevalence less than 10%. Laboratories have begun to demonstrate that SARS‐CoV‐2 can be detected in RT‐qPCR performed on pooled samples, despite potential dilution.…”
Section: Discussionsupporting
confidence: 91%
“…While pooling of samples has been widely proposed as a way to expand testing capacity for large scale screening [9][10][11] , there has been limited empirical evidence on pooling performance to properly inform projections of both feasibility and cost-effectiveness. Therefore, we investigated the potential of pooling saliva for SARS-CoV-2 detection in the laboratory setting, then used our findings to inform a model exploring the benefits of pooled sample testing at different rates of virus prevalence in the population.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy many countries have adopted to increase testing capacity is to combine samples into pools that are tested together [1,2,3,4,5]. If such a pool is tested negative, all individual samples within the pool are declared free of SARS-CoV-2, whereas if it is tested positive then all individuals in that pool must be retested individually in a second round.…”
Section: Introductionmentioning
confidence: 99%